2018
DOI: 10.1021/acs.jmedchem.7b01261
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-((7H-Pyrrolo[2,3-d]pyrimidin-4-yl)amino)-N-(4-((4-methylpiperazin-1-yl)methyl)phenyl)-1H-pyrazole-3-carboxamide (FN-1501), an FLT3- and CDK-Kinase Inhibitor with Potentially High Efficiency against Acute Myelocytic Leukemia

Abstract: A series of 1-H-pyrazole-3-carboxamide derivatives have been designed and synthesized that exhibit excellent FLT3 and CDK inhibition and antiproliferative activities. A structure-activity-relationship study illustrates that the incorporation of a pyrimidine-fused heterocycle at position 4 of the pyrazole is critical for FLT3 and CDK inhibition. Compound 50 (FN-1501), which possesses potent inhibitory activities against FLT3, CDK2, CDK4, and CDK6 with IC values in the nanomolar range, shows antiproliferative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 46 publications
(82 reference statements)
2
46
0
Order By: Relevance
“…In our study, the mice treated dose with the system or with Ara-C 50 (mg/kg)/day. In the MV4-11 model, the group mice injected with 50 (mg/kg)/day of cytarabine only had reduced tumor growth rates, and the tumor-growth inhibition was 61.94% on the 21st day [ 41 ]. And also, there is reported that oral Berberine 200 (mg/kg/day) for 3 weeks statistically significantly reduced the size and weight of spleen in these animals and also reduced the percentage of MAC-3 and CD11b cells in the blood [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the mice treated dose with the system or with Ara-C 50 (mg/kg)/day. In the MV4-11 model, the group mice injected with 50 (mg/kg)/day of cytarabine only had reduced tumor growth rates, and the tumor-growth inhibition was 61.94% on the 21st day [ 41 ]. And also, there is reported that oral Berberine 200 (mg/kg/day) for 3 weeks statistically significantly reduced the size and weight of spleen in these animals and also reduced the percentage of MAC-3 and CD11b cells in the blood [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…One week after leukemia cell injection, all mice were randomly divided into five groups (PBS control, Blank SNE control, BBR, Ara-C, BBR SNE, n = 10). All animals were treated at the same dose of 50 (mg/kg)/day for 14 days by oral administrated with PBS, Blank SNE, BBR, and BBR SNE except Ara-C was administrated by tail vein injection, referring to the effect dose of Ara-C in the MV4-11 model [ 41 ]. During 98 days of observation, the survival time and number of all mice were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 54 is safer acute‐toxicity studies in mice (LD 50 = 186 mg/kg). In addition, injections of 54 at 30 (mg/kg/d) significantly induced tumor regressions, and the percent‐tumor‐regression rate on the 21st day was 78.95% …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 98%
“…In addition, injections of 54 at 30 (mg/kg/d) significantly induced tumor regressions, and the percent-tumor-regression rate on the 21st day was 78.95%. 55 On the basis of the binding model of 54 in the adenosine triphosphate (ATP)-binding site of FGFR3, the indazole scaffold is located in the binding pocket and makes hydrogen bonds with Ala232 and Glu230; the vinyl pyrazole moiety extends toward the solvent, forming key hydrophobic interactions. On the basis of a binding model of compound 55 in the ATP-binding site of FGFR1 with a disclosed crystal structure of the FGFR1 kinase domain (PDB ID: 3WJ6), the benzimidazole fragment is considered to extend from the indazole 3-position toward the solventexposed region.…”
mentioning
confidence: 99%
“…proposed CRBN‐based PROTACs to degrade CDK2, [ 102 ] using two pan CDK inhibitors, AT7519 [ 131 ] and FN‐1501. [ 132 ] With the two inhibitors, they tested several linkers to determine their optimal lengths and compositions. A first screening of 20 compounds in PC‐3 cells showed that two compounds in the AT7519 series induced a selective degradation of CDK2 at 1 × 10 −6 m for 12 h. However, compound 5j (Figure 5) was selective for CDK2 at 5 × 10 −6 m , while the other also degraded CDK9 at the same concentration.…”
Section: Serine‐threonine Kinases (Stks) Degradersmentioning
confidence: 99%